RESILIÊNCIA DE ATLETAS DE BASQUETEBOL - Pelosini, David Eduardo (2013)
Resilience is the individual´s ability to adapt oneself positively to the adversities of life, coping and better functioning with them. This construct has been studied for over forty years in Psychiatry with focus on children, but its investigation with adults is more recent. In the sports field studies have hardly begun. The sports arena presents great challenges and constant adversities which athletes have to conquer in order to accomplish professional goals; consequently, they frequently have to deal with their physical and psychological limitations. Therefore, resilience can be an important aspect in the athletes´ professional lives. This study aims at identifying the relationship between resilience and basketball statistics efficiency. Seventy one adult professional and active basketball athletes have volunteered to take part in this research. The variables were assessed through the Evaluation Scale of Resilience EAR a questionnaire of socio demographic data and performance indexes registered by the Paulista Federation of Basketball. The answers from the participants were coded on a spreadsheet of SPSS and submitted to descriptive statistical analyses and to the calculus of Pearson bi-varied correlations so as to identify the associations between the athletes and their level of resilience. The results of the descriptive statistical analysis and the Pearson bi-varied correlation revealed that the athletes demonstrated high level of resilience with emphasis given to persistence in face of difficulties and a positive attitude towards change. Factors which comprise resilience showed no significant correlation regarding the athletes´ efficiency. As the averages were compared through variant analysis, it was noticed that the athletes that had between five and ten years practice presented better efficiency coefficient average. Results also revealed that the athletes, who played less than 8 minutes in a match, produce, on average, lower indexes of statistical efficiency and the athletes who belong to teams of medium results in the classification table are likely to have a better perception of personal competence than the athletes who play in worse placed teams. Resilience factors did not differ in relation to the athletes experience or to the average time spent in the court. The results of this study reveal the need to question whether statistical efficiency indicators are the most adequate criteria to establish the role of resilience in the life of Basketball players and point to the need of further studies regarding the influence of individual characteristics in the professional sports world.